2018
DOI: 10.1136/emermed-2017-207238
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of accidental hypothermia in Japan: the J-Point registry

Abstract: Active prevention and intervention should occur for this important public health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 17 publications
3
55
0
3
Order By: Relevance
“…This indicates that the patients in the Japanese studies were notably sicker than the patients reported in the European studies. Finally, the overall mortality rate was 24.4% and did not vary between the three hypothermia groups 1. In the Matsuyama study, 4.8% of the patients1 and in the Morita study 10.2%3 arrested during rewarming compared with no one in the European studies.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…This indicates that the patients in the Japanese studies were notably sicker than the patients reported in the European studies. Finally, the overall mortality rate was 24.4% and did not vary between the three hypothermia groups 1. In the Matsuyama study, 4.8% of the patients1 and in the Morita study 10.2%3 arrested during rewarming compared with no one in the European studies.…”
mentioning
confidence: 75%
“…In the European studies, most hypothermia cases occur outdoors (up to 100%). Third, most cases of the Matsuyama study1 were secondary hypothermia as opposed to primary hypothermia in Europe. Fourth, in the Matsuyama study1 besides being older, patients were frail and they suffered from one or more comorbidities.…”
mentioning
confidence: 99%
See 3 more Smart Citations